2006
DOI: 10.1037/0033-2909.132.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Meditation states and traits: EEG, ERP, and neuroimaging studies.

Abstract: Neuroelectric and imaging studies of meditation are reviewed. Electroencephalographic measures indicate an overall slowing subsequent to meditation, with theta and alpha activation related to proficiency of practice. Sensory evoked potential assessment of concentrative meditation yields amplitude and latency changes for some components and practices. Cognitive event-related potential evaluation of meditation implies that practice changes attentional allocation. Neuroimaging studies indicate increased regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
770
11
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,320 publications
(853 citation statements)
references
References 306 publications
54
770
11
18
Order By: Relevance
“…Since 2004, research in education began to focus on mindfulness for general wellbeing for all which has also been a recent focus for health related studies. Benefits included reduced anxiety and emotion regulation noted in reductions in stress-cortisol (Willis, 2007;Fogarty, 2009) and a thickening of the prefrontal cortex which is associated with emotion regulation (Lazar et al, 2005;Cahn & Polich, 2006). Yook et al (2008) found through a series of questionnaires that participants reported improved sleep patterns.…”
Section: Benefits Of Mindfulnessmentioning
confidence: 99%
“…Since 2004, research in education began to focus on mindfulness for general wellbeing for all which has also been a recent focus for health related studies. Benefits included reduced anxiety and emotion regulation noted in reductions in stress-cortisol (Willis, 2007;Fogarty, 2009) and a thickening of the prefrontal cortex which is associated with emotion regulation (Lazar et al, 2005;Cahn & Polich, 2006). Yook et al (2008) found through a series of questionnaires that participants reported improved sleep patterns.…”
Section: Benefits Of Mindfulnessmentioning
confidence: 99%
“…(Vaitl et al, 2005, pp. 98-127;Cahn & Polich, 2006;"Meditation," 2012). "Meditation refers to a family of self-regulation practices that focus on training attention and awareness in order to bring mental processes under greater voluntary control and thereby foster general mental well-being and development and/or specific capacities such as calm, clarity, and concentration."…”
Section: The Concept Of Meditationmentioning
confidence: 99%
“…The mantra is thought to eventually occupy awareness during meditative practice without concentrative effort; thereby possibly distinguishing the technique from other concentrative practices (Mahesh Yogi as cited in Cahn & Polich, 2006;Travis, Tecce, Arenander, & Wallace, 2002). Transcendental meditation involves the continuous chanting of a mantra, until a dream -like state of mind is attained.…”
Section: The Concept Of Meditationmentioning
confidence: 99%
“…Second, although there is consensus within the philosophy and psychology of religion that spiritual experiences-like all other types of experiences-are largely dependent on social, cultural or religious context [55], it is also important to recognize these experiences as psychophysiological events that involve, and are mediated by, peripheral and central neural (and neuroendocrine and/or neuroimmunological) substrates [56,57]. In the main, it appears that spiritual practices-and experiences-engage hierarchical activation of peripheral and central neuraxes, which involve iterative complexification of signal processing, from sensory transduction/transmission to (ultimately) cognitive and emotional perceptions and ideation.…”
Section: Investigating the Relationship Between Spirituality And Healthmentioning
confidence: 99%